2021
DOI: 10.48550/arxiv.2106.12082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypergraphs with no tight cycles

Abstract: We show that every r-uniform hypergraph on n vertices which does not contain a tight cycle has at most O(n r−1 (log n) 5 ) edges. This is an improvement on the previously best-known bound, of n r−1 e O( √ log n) , due to Sudakov and Tomon, and our proof builds up on their work. A recent construction of B. Janzer implies that our bound is tight up to an O((log n) 4 log log n) factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Given a 3-graph G, let p(G) denote the number of 1-dimensional faces of G, that is, the number of pairs of vertices which appear in an edge. As proved by Letzter [33], slightly improving the result of Sudakov and Tomon [42], if a 3-graph G satisfies e(G) = Ω(p(G)(log p(G)) 5 ), then G contains a tight cycle. A similar strengthening of Theorem 1.5 also holds.…”
Section: Cycles In Simplicial Complexesmentioning
confidence: 82%
See 1 more Smart Citation
“…Given a 3-graph G, let p(G) denote the number of 1-dimensional faces of G, that is, the number of pairs of vertices which appear in an edge. As proved by Letzter [33], slightly improving the result of Sudakov and Tomon [42], if a 3-graph G satisfies e(G) = Ω(p(G)(log p(G)) 5 ), then G contains a tight cycle. A similar strengthening of Theorem 1.5 also holds.…”
Section: Cycles In Simplicial Complexesmentioning
confidence: 82%
“…This was disproved in a strong sense by B. Janzer [17], who showed that an r-graph on n vertices can have Ω(n r−1 log n/ log log n) edges without containing a tight cycle. On the other hand, Sudakov and Tomon [42] proved the upper bound n r−1+o (1) , which was further improved by Letzter [33] to O(n r−1 (log n) 5 ). However, none of these proofs seem to extend to give any bounds on the extremal numbers of tight cycle of fixed length ℓ. Verstraëte [43] proposed the conjecture that if r divides ℓ, then any r-graph with n vertices containing no tight cycle of length ℓ can have at most O(n r−1+(r−1)/ℓ ) edges.…”
Section: Cycles In Simplicial Complexesmentioning
confidence: 96%
“…To show that there is a short rainbow x, y-path in G, we first apply tools due to Jiang, Methuku and Yepremyan [5] and Letzter [8] to show that there is a set of vertices U of size Ω(n) such that for each v ∈ U there is such a short rainbow x, v-path P (v) and a short rainbow y, v-path Q(v), both of which avoid C, such that no colour is used on too many of these paths P (v) and Q(v). It easily follows that for almost all pairs (u, v) with u, v ∈ U , the paths P (u) and Q(v) are colour-disjoint.…”
Section: Overview Of the Proofsmentioning
confidence: 99%
“…We also prove a strengthening of Theorem 1.2, regarding 'rooted' rainbow subdivisions of K m in expanders (see Theorem 6.1). For this stronger version, in addition to the ingredients used for proving Theorem 1.2, we use the framework of [5] and an additional idea used by Letzter in [8] (see Lemma 3.7).…”
Section: Introductionmentioning
confidence: 99%
“…Turán type problems for tight cycles have a long history, dating back to an old question of Sós (see [21]), and appear in relation to seemingly unrelated topics [4]. We refer the reader particularly to the report [21] from the 2011 American Institute of Mathematics (AIM) workshop "Hypergraph Turán Problem", which contains many such problems, and to [15,16,19,34] for some recent specific results. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%